Implementation of Social Care Character in Students Through Koin Peduli Sahabat Activities in Elementary Schools - Radiyem Radiyem; Ana Andriani (Proceedings Series on Social Sciences & Humanities, 2023)
This study aims to describe the implementation process of "Koin Peduli Sahabat" activities to improve the character of social care in elementary school students. Initial observations show that students' understanding and awareness of social care character is still lacking, the application of social care character is not optimal, and support from teachers is still low. The method used in this research is a qualitative approach with case studies. The subjects in this study were grade VI students of SDN Bangkal 01 in Binangun District, Cilacap Regency. Data collection techniques with interviews, observations, and documentation studies. Activities in data analysis are data reduction, data presentation, and conclusions. The results showed that the implementation of "Koin Peduli Sahabat" activities can improve the character of social care in elementary schools.